RESPON TRAKEOSPASMOLITIK EKSTRAK METANOL DAUN Macaranga lamellata Whitmore SECARA IN VITRO - Afandi, Irvan; Astuti, Winni; Marliana, Eva (JURNAL ATOMIK, 2022)
The research about in vitro trakeospasmolytic response of methanol extract of Macaranga lamellata Whitmore leaves was carried out. This research was conducted to determine the spasmolytic effect of the methanol extract of Macaranga lamellata Whitmore leaves on changes in separate organ of the guinea pig ring tracheal. The methods used include the bioassay isolated organ with two groups of treatment, control group and extract group. Methanol extract was given cumulatively on the organ bath. Positive control is used aminofilin and negative control is used DMSO solvent. Phytochemical test results showed that total methanol extract contained alkaloids, polyphenol, steroids, flavonoids dan saponins while phytochemical test results showed on ethyl acetate fraction contained alkaloids, polyphenol, steroids, quinons dan flavonoids. The Percentage change in tracheal smooth muscle as a spasmolytic response by using methanol extract with cumulative concentration of 0.3, 1 dan 3 mg/mL respectively -24.925%; -29.865% and -36.795% . This research is shown methanol extract of Macaranga lamellata Whitmore leaves have antiasthma effect based on the tracheospasmolytic activity. Keywords: Antiasthma, Bioassay isolated organ, Macaranga lamellata Whitmore, Marmot, Trakeopasmolytic.